Effect of Lysinibacillus isolated from environment on probiotic properties and gut microbiota in mice - Zhibo Zeng; Wen Yue; Cermon Kined; Bakint Raciheon; Jing Liu; Xinzhu Chen (Ecotoxicology and Environmental Safety, 2023)
Soil microorganisms (SM) are primarily involved in organism degradation, plant nitrogen nutrient immobilization, host microorganisms and oxidation. However, research on the effect of soil-derived Lysinibacillus on the intestinal microbiota spatial disparity of mice is lacking. To test the probiotic properties of Lysinibacillus and the spatial disparity on mice intestinal microorganisms, hemolysis test, molecular phylogenetic analysis, antibiotic sensitivity testing, serum biochemical assays and 16S rRNA profiling were applied. The results showed that Lysinibacillus (LZS1 and LZS2) was resistant to two common antibiotics, Tetracyclines and Rifampin, and sensitive to other antibiotics among the 12 antibiotics tested and negative for hemolysis. In addition, the body weight of group L (treatment of Lysinibacillus, 1.0 × 108 CFU/d for 21days) mice was significantly greater than that of the control group; serum biochemical tests showed that the TG and UREA were significantly lower in group L. The spatial disparity of intestinal microorganisms in mice was significant, treatment of Lysinibacillus (1.0 × 108 CFU/d for 21days) reduced the intestinal microbial diversity and decreased the richness of Proteobacteria, Cyanobacteria and Bacteroidetes in mice. Furthermore, Lysinibacillus treatment enhanced Lactobacillus and Lachnospiraceae richness and significantly reduced 6 bacterial genera in jejunum community, reduced 8 bacterial genera, but increased bacteria at the 4 genera level in cecum microorganisms. In conclusion, this study demonstrated spatial disparity of intestinal microorganisms in mice and probiotic potential of Lysinibacillus isolated from soil.